The Grassland Ecological Compensation Policy Drives the Differentiation of Herders’ Livelihoods in Inner Mongolian Desert Grassland - Hong Chang; Xinchao Liu; Yu Xie; Yahong Liu; Wu Yang; Jianming Niu (Agriculture, 2022)
Herders’ livelihood strategies are functions of the capitals at their disposal. Although this thesis has been proved, it has not been applied to livelihood research in the context of conservation initiatives. The Chinese government implemented the Grassland Ecological Compensation Policy (GECP) in 2011. However, the impact of the policy on herders’ livelihoods is still unclear. This study measured the variation in herders’ livelihood strategies in the desert grassland of Inner Mongolia, China, after the implementation of the GECP. This study also analyzed the impacts of livelihood capitals on the livelihood strategies, revealing the shortages of different livelihood strategies. The results showed the following: After the GECP, (1) herders’ livelihood strategies could be grouped into five types based on livelihood capitals. The livelihood capitals of herders varied greatly, resulting in large economical gaps among households with different livelihood strategies. (2) The herders’ livelihood strategies were affected by factors including the education, age, social communication, amount of livestock, income, and subsidy of the herders. (3) The main income sources of different livelihood strategies were both subsidy and livestock husbandry. In general, the GECP drives the differentiation of herders’ livelihoods remarkably. Future conservation initiatives should take the shortages of different livelihood strategies into account.